1983
DOI: 10.1093/jn/113.9.1756
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Tryptophan Deficiency on Thyroid Gland, Growth Hormone and Testicular Functions in Chickens

Abstract: Broiler chicks from 2 to 4 weeks of age were fed control (0.23%) and deficient (0.115, 0.058%) levels of L-tryptophan. Separate groups of control chicks were pair-fed daily with the deficient chicks. Deficient chicks grew less efficiently than did pair-fed controls. Plasma triiodothyronine (T3) was elevated in deficient chicks, especially compared to pair-fed controls, and this was accompanied by lower reverse T3. Plasma thyroxine (T4) was also reduced with 0.059% tryptophan. However, thyroid weights and folli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

1984
1984
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 33 publications
2
13
0
1
Order By: Relevance
“…Blood 5-HT levels were measured since they have been related with misbehaviour (feather pecking) in layers and BW gain in broilers, respectively (Carew et al, 1983). Relations between behavioural responses and 5-HT were also reported for broilers (Kostal and Savory, 1996;Shea-Moore et al, 1996).…”
Section: Discussionmentioning
confidence: 98%
“…Blood 5-HT levels were measured since they have been related with misbehaviour (feather pecking) in layers and BW gain in broilers, respectively (Carew et al, 1983). Relations between behavioural responses and 5-HT were also reported for broilers (Kostal and Savory, 1996;Shea-Moore et al, 1996).…”
Section: Discussionmentioning
confidence: 98%
“…Plasma thyroxine (T4) was analyzed by double antibody radioimmunoassay (RIA) as described previously (Carew et al, 1983). Plasma 3,5,3'triiodothyronine (T 3 ) was analyzed by single antibody RIA with Gamma Coat tm RIA kits (Clinical Assays, Cambridge, MA.).…”
Section: Methodsmentioning
confidence: 99%
“…Protein restricted chickens are characterized by a reduced plasma T 4 and increased plasma T 3 level (Buyse et al, 2001). Carew et al (1983; reported that dietary deficiencies of some individual essential amino acids may affect thyroid function in chicks. have categorized the mechanisms by which protein and essential amino acid deficiencies alter thyroid function in several animal species.…”
Section: Introductionmentioning
confidence: 99%